Proyecto de branding para clave alta, agencia de marketing digital: manual de identidad y contenido para redes - Milussich Fernández, Ariadna (2024)
The work to be presented consists of a proposal for the launch of the Clave Alta brand, a digital marketing agency, which includes the development of the identity through a brand manual and the digital communication campaign based on the analysis of the target audience, the competition , and the value proposition provided by the company. The proposal of the marketing strategy in social networks, content and communication campaign was based on the analysis of what the agency was looking for as a brand and the previous research of trends in social networks. Within the project's launch campaign, content was produced that included video recording for reels on the networks, and graphic design for publications to be launched. Validations were carried out at the client, expert and general public level to optimize the visual pieces and actions.